2010
DOI: 10.1038/ejhg.2010.181
|View full text |Cite
|
Sign up to set email alerts
|

LTBP2 and CYP1B1 mutations and associated ocular phenotypes in the Roma/Gypsy founder population

Abstract: Primary congenital glaucoma (PCG) is a genetically heterogeneous autosomal recessive disorder, which is an important cause of blindness in childhood. The first known gene, CYP1B1, accounts for a variable proportion of cases in most populations. A second gene, LTBP2, was recently reported in association with a syndrome, in which glaucoma is secondary to lens dislocation. We report on the molecular and clinical profile of 34 families diagnosed as PCG, all originating from the Roma/ Gypsy founder population. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 40 publications
(58 reference statements)
0
39
0
Order By: Relevance
“…14,17,18 The Indian component of the proto-Roma ancestry was supported by the identification of disease-causing mutations described in affected subjects in India and Pakistan. 9,15,19,20 Furthermore, the Roma show high frequencies of the H-M69 Y-chromosome 4,17,21,22 and mitochondrial DNA (mtDNA) M5, M18, M25, and M35 haplogroups 4,7,17,[23][24][25] reported to have an Indian origin. 25,26,27 Accordingly, studies of autosomal markers identified the Northwest of India as the most probable homeland of the European Roma.…”
Section: Introductionmentioning
confidence: 99%
“…14,17,18 The Indian component of the proto-Roma ancestry was supported by the identification of disease-causing mutations described in affected subjects in India and Pakistan. 9,15,19,20 Furthermore, the Roma show high frequencies of the H-M69 Y-chromosome 4,17,21,22 and mitochondrial DNA (mtDNA) M5, M18, M25, and M35 haplogroups 4,7,17,[23][24][25] reported to have an Indian origin. 25,26,27 Accordingly, studies of autosomal markers identified the Northwest of India as the most probable homeland of the European Roma.…”
Section: Introductionmentioning
confidence: 99%
“…It regulates the assembly of elastic fibers through binding to DANCE/fibulin‐5 and its expression appears to be increased in intrinsically aged skin . In human cancer, LTBP2 has been suggested to act as a suppressor in oesophageal squamous cell carcinoma and is up regulated in human pancreatic ductal adenocarcinoma . In a recent study that used proteomics to characterize cancer‐associated fibroblasts in a mouse model of colorectal carcinogenesis, LTBP2 was identified as one of the components of a desmoplastic signature of four markers that significantly increased in tumor stroma, without significant expression in the cancer epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…LTBP2 , latent transforming growth factor beta binding protein 2 (LTBP2) , located in the GLC3C locus, was reported to be associated with PCG by two different studies and confirmed by Azmanov et al (Ali et al, 2009; Azmanov et al, 2010; Narooie-Nejad et al, 2009). Three LTBP2 mutations were reported as either frameshift or nonsense mutations.…”
Section: Primary Congenital Glaucomamentioning
confidence: 77%